Karma as a Means of Wartime Political Mobilization: A Reading of Chinese Buddhists’ Response to the Second Sino-Japanese War, 1937-1945 - Joey Yiqiao Yan (Journal of Global Buddhism, 2023)
The concept of karma is of great significance for scholars of modern China seeking to comprehend the impact of Buddhism on the Second Sino-Japanese War. This paper explores the sociopolitical function of karma within China’s wartime society and its profound implications for Nationalist politics. It examines how karma was articulated by wartime Chinese Buddhists as a means of Nationalist mobilization for China's war effort. Moreover, this paper situates the discourse on karma within the framework of modern nationalism by comparing the sociopolitical utilization of karma by Chinese and Japanese Buddhists during the war. As such, it reveals that the divergent interpretations of karma by Buddhists in the two nation-states had enduring and far-reaching consequences on their respective societies.